ELECTRONIC MEDICATION TO MINIMIZE MEDICATION ERROR AND IMPROVE PATIENT SAFETY IN HOSPITAL: A SYSTEMATIC REVIEW - Ayatulloh, Daviq; Priyantini, Diah; Nursalam, Nursalam; Basri, Ahmad Hasan (Universitas Muhammadiyah Surabaya, 2024)
Introduction: Quality is the main focus of attention in health services, one of the factors that can lower the quality of health care and patient confidence is the fault of the medication. A medication error is an event that can lead to an error in giving care to patient. This study aimed to review electronic medication to minimize medication error and patient safety in hospital. Methods: A systematic review was carried out in order to get a comprehensive perspective on benefit using electronic medication to minimize medication error. Literature search was performed through English databases of Scopus, PubMed, ProQuest and Sciencedirect within in the last 5 years. This search was conducted between November, 2021 until January, 2022. The type of study design was excluded the review and descriptive articles. All document and studies providing evidence regarding electronic medication in hospitals were included in this review. Results: Overall, the review consists of 15 articles which studies the electronic system affects to medication error and improve patient safety. Finding obtained the intervention can be used and applied to improve patient safety such as EMMS (Electronic Medication Management Systems), EHR/EHRs (Electronic Health Reports), E-Prescribing (Electronic Prescribing), MediDocQ (Medication Administration Charts), and CPOE (Computerized Provider order entry). Conclusions: Health information technology in the field of medicine has proven to be effective in reducing medication errors in hospital patients. So that through this review, it is expected to be able to improve the competence of health workers and reduce the risk of medication errors.